Scaffolding process Based on Diagnosis Students Difficulties in Solving Linear Program by Using Mapping Mathematic - Mustaqim Mustaqim (Pascasarjana Universitas Negeri Malang (UM), 2013)
Proses Scaffolding Berdasarkan Diagnosis Kesulitan Siswa dalam Menyelesaikan Masalah Program Linear dengan Menggunakan Mapping Mathematic Abstract: Diagnosis difficulties are important for teachers in teaching. By making a diagnosis, the teacher can know in which part of students experiencing difficulties and then provide appropriate alternative solutions. Diagnosis can be done by using mathematic mapping. The subjects were students of class XI Agribusiness Program Ruminant SMKN I Maesan Bondowoso as many as six students were selected based on an error in diagnostic tests and communication skills. This research data is the result of students' work, recording during the test and the scaffolding, important notes, and sheets scaffolding. Accumulated data is done by testing techniques, interviews, and provide scaffolding. The provision of scaffolding in this study as the scaffolding strategies expressed by Anghilery. Activity data analysis is a data reduction step, step presentation of data, and conclusions step data. Based on the results of the study, it is found that the provision of scaffolding in part difficult experienced by students can reduce / eliminate the difficulties students. Key Words: diagnosis, mapping mathematic, scaffolding Abstrak: Diagnosis kesulitan merupakan hal yang lebih penting bagi guru dalam mengajar. Dengan melakukan diagnosis, guru dapat mengetahui di bagian mana siswa mengalami kesulitan dan kemudian memberikan alternatif solusi tepat. Diagnosis bisa dilakukan dengan menggunakan mapping mathe-matic. Subjek penelitian ini adalah siswa kelas XI Program Agribisnis Ternak Ruminansia SMKN I Maesan Bondowoso sebanyak 6 siswa yang dipilih berdasarkan kesalahan dalam tes diagnosis dan kemampuan komunikasi. Data penelitian ini adalah hasil karya siswa, rekaman selama tes dan proses scaffolding, catatan penting, dan lembaran scaffolding. Akumulasi data dilakukan dengan uji teknik, wawancara, dan memberikan scaffolding. Pemberian scaffolding dalam penelitian ini seperti dalam strategi scaffolding yang dinyatakan oleh Anghilery. Aktivitas analisis data adalah langkah reduksi data, langkah penyajian data, dan langkah kesimpulan data. Berdasarkan hasil penelitian ditemukan bahwa pemberian scaffolding di bagian sulit yang dialami siswa dapat mengurangi/menghilangkan kesulitan siswa.Kata kunci: diagnosis, mapping mathematic, scaffolding